KONTRIBUSI AUDIT INTERNAL TERHADAP EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN BAHAN BAKU (STUDI KASUS PADA PT. SSG) - Amrulloh, Amrulloh; Jasmadeti, Jasmadeti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to evaluate the extent to which internal audit contributes to the effectiveness of the internal control system over raw material inventory at PT SSG. The research method used is qualitative, with a descriptive-analytical approach. The data analysis technique refers to the theory of Miles and Huberman, involving direct interviews with internal auditors at PT SSG as the primary data source. The results of the study indicate that internal audit plays a significant role in supporting the effectiveness of the internal control system over raw material inventory. This is evidenced by the fulfillment of key effectiveness indicators, as outlined in the theoretical framework used in this research.